Gambaran Tingkat penggunaan Obat Generik dan Obat Paten di Depo Rawat Jalan Instalasi Farmasi RSUD Arifin Nu’mang Kabupaten Sidenreng Rappang - Fitriana Bunyanis; Nur Astuti Wulandari (Strada Journal of Pharmacy, 2021)
This study aims to determine the level of use of generic drugs and patent drugs in outpatient depots of the pharmacy installation at Arifin Nu'mang Hospital, Sidenreng Rappang Regency with descriptive research methods. Descriptive method is a method that serves to describe or provide an overview of the object under study through the sample and population. From the results of the research that has been done, the percentage of generic drugs was obtained as much as 75.42%, while the percentage of patent drugs was 24.38%. The percentage of generic drugs has not met the stipulated provisions. This can be caused by several things, one of which is the patient asking the doctor to write a patent drug prescription.